The Effect of Physiotherapy on Erectile Dysfunction Secondary to Prostatic Adenectomy: A Randomized Control Trial Study - Afshar Safavi, Mahdi; Niknam, Hoda; Okhovatian, Farshad; Akbarzadeh Baghban, Alireza; Naimi, Sedigheh Sadat; Roostayi, Mohammad Mohsen (Urology Journal, 2024)
Purpose: The objective of this randomized controlled trial was to investigate the impact of manual therapy (friction massage) and pelvic floor muscle (PFM) training on erectile dysfunction (ED), pelvic floor muscle thickness, and blood flow in the penile arteries and veins in men who have undergone prostatic adenectomy (PA). Materials and Methods: This study employed a randomized, double-blinded, controlled trial design. Forty patients participated and were divided into two groups: intervention and control (n=20 per group). The intervention group received 10 sessions of pelvic floor muscle training and manual therapy, while the control group solely underwent pelvic floor muscle training. The recovery rate was measured using the International Index of Erectile Function 15 (IIEF-15) questionnaire and Erection Hardness Score (EHS). Sonographic factors were assessed using simple and Doppler ultrasound. Results: The intervention group exhibited significantly higher erectile function scores (F(1,37)=158.04, P < 0.001, η2 P = 0.810) and a higher average total (IIEF-15) score (20.52) (F(1,37)=136.76, P < 0.001, η2 P = 0.787) compared to the control group in the post-test assessment. Comparison between the two groups revealed an increase in ultrasonic parameters such as the thickness of the ischiocavernosus and bulbospongiosus muscles, maximum systolic velocity, and minimum diastolic velocity of the cavernosal artery in the intervention group. However, the maximum blood flow velocity in the posterior vein decreased. Conclusion: PFM training and friction massage play a significant role in managing ED following PA, positioning them as the primary treatment approach for men experiencing ED post-prostatectomy.